2021 IEEE BiCMOS and Compound Semiconductor Integrated Circuits and Technology Symposium (BCICTS) 2021
DOI: 10.1109/bcicts50416.2021.9682466
|View full text |Cite
|
Sign up to set email alerts
|

InP DHBT Characterization up to 500 GHz and Compact Model Validation Towards THz Circuit Design

Abstract: We report on-wafer characterization results up to 500 GHz on a 0.4×5 µm² InP/InGaAs DHBT. The measurements were performed using an on-wafer Thru-Reflect-Line (TRL) calibration kit especially developed in this technology. The resulting measurements allowed to validate both the RF performance of the 0.4-µm InP/InGaAs DHBT fabricated by III-V Lab, featuring 390/600 GHz fT/fmax, and the HiCuM compact model towards future circuit design at submillimeter-wave frequencies thanks to 90% typical yield reached in this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…2) High quality pads (design 2) As presented in [5], this design (see Fig. 3) combines two optimization strategies to improve the on-wafer measurement accuracy up to 500 GHz.…”
Section: Fig 2 Photograph Of a Die With High Density Padsmentioning
confidence: 99%
See 1 more Smart Citation
“…2) High quality pads (design 2) As presented in [5], this design (see Fig. 3) combines two optimization strategies to improve the on-wafer measurement accuracy up to 500 GHz.…”
Section: Fig 2 Photograph Of a Die With High Density Padsmentioning
confidence: 99%
“…It has been shown that measurements beyond 110 GHz are particularly difficult [4]. To perform InP DHBT characterization at higher frequencies, on-wafer thru-reflectline (TRL) calibration has been introduced along with optimized test structures [5]- [7]. This method has demonstrated excellent results.…”
Section: Introductionmentioning
confidence: 99%
“…However, the fact remains unchanged that accurate characterization at higher frequencies are needed to confirm the cut-off frequencies as well as to extract and validate the associated device compact model, and thus enabling the design of sub-millimeter-wave integrated circuits. Some previous works have already demonstrated InP DHBT characterization beyond 300 GHz [4], [5] using less conventional methods such as on-wafer calibration. With the emergence of 220 GHz broadband vector network analyzer (VNA) [6], it is now being considered feasible to fully characterize a wafer up to 220 GHz.…”
Section: Introductionmentioning
confidence: 99%